1965 transactions of the Third International Vacuum Congress, 28 June-2 July 1965, Stuttgart, Germany. - Adam, Hans (Pergamon Press, 1967)
1965 Transactions of the Third International Vacuum Congress, Volume 2, Part I documents the proceedings on the Third International Vacuum Congress held in Stuttgart, Germany on June 28-July 2, 1965. This compilation is divided into four sessions. Session 1 focuses on evaporation and thin films, while Session 2 deals with the flow of gases. The components and materials of orthodox vacuum pumps are covered in Session 3. The last session concentrates on pressure measurement and leak detection. The topics discussed include developments in the vacuum deposition of electronic film circuits; bulk su.